Laguna Beach Marketing Communication Strategy in Increasing Tourist Visits by the Kaur Regency Tourism Office - Melky Alex Suhendra; Vethy Octaviani; Yusuarsono Yusuarsono (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The aim of the research was to determine the marketing communication strategy of Laguna Beach in increasing tourist visits by Kaur Regency Tourism Office. The method used in this research was qualitative descriptive research. Informants in this research amounted to 5 people consisting of 2 key informants and 3 main informants, the results of the research were in accordance with the theory of Marketing Mix Marketing Communication Strategy: (Morisan 2015: 141) includes: 1.) Product, the tourism office and the manager of BUMDes Laguna Beach offer the natural beauty of white sand, rock gardens, and clean and clear sea water so that coral and small fish can be seen nesting beside the rocks. 2) Price determination of the entrance fee for Laguna Beach tourism object based on the Regent's regulation which stipulates that the results of deliberations between the tourism office and the manager are reported to the Regent to make regulations which make a strong and binding legal basis to be implemented by both the agency and the manager. 3) Place, Laguna Beach is very strategic because it is located on the side of the Sumatra highway, so the access is faster and does not require a lot of money for visitors to travel. 4) Promotion, in promoting the beach tourist attraction, the tourism service and managers use social media, namely Instagram and Facebook. 5) People, there is a direct involvement from the tourism office, especially the promotion section, DKP and tourism ambassadors who work together in promoting existing tourist objects including the beach tourist attraction. 6) Packaging for tour packages organized by the tourism office in collaboration with the management, namely BUMDes, has received a very good response from the community at a fee set by the tourism office and management to use the facilities by paying for tour packages. But unfortunately, that until now the tourism office has not been able to implement this package. 7) The program held by the Tourism Office was very effective but the 2022 program was not implemented because the activity was moved to Lapangan Merdeka. 8) Partnership, the existence of cooperation partners carried out by the village government to the City Regency Tourism Office, Provincial Office and tour trips to advance tourist objects on Laguna Beach.